2007
DOI: 10.1097/01.qai.0000243126.75153.3c
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Parental Death Among Young People in South Africa and Risk for HIV Infection

Abstract: More than one quarter of young South Africans have experienced parental death. Death of a parent is associated with young female South Africans' HIV status and sexual behaviors among young female and male South Africans. HIV prevention interventions are necessary to address the specific needs of young South Africans who have experienced parental death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 15 publications
(13 reference statements)
5
76
0
Order By: Relevance
“…The patterns showing higher risk sexual behavior among adolescents living in households where an adult is infected with HIV are consistent with patterns for adolescent orphans observed in recent studies in various Southern Africa settings where greater sexual risk (ever had sex, ever pregnant) was observed among orphans than non-orphans (Thurman, et al, 2006;Operario et al, 2007;Nyamu-kapa et al, 2008;Birdthistle et al, 2009). It is possible that HIV infection among adults is households will lead to an increased risk of adolescents engaging in high-risk sexual behaviors due to homes being destabilized or impoverished by HIV/AIDS (Enaik et al, 2002;Oman et al, 2005;Sturgeon, 2008).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The patterns showing higher risk sexual behavior among adolescents living in households where an adult is infected with HIV are consistent with patterns for adolescent orphans observed in recent studies in various Southern Africa settings where greater sexual risk (ever had sex, ever pregnant) was observed among orphans than non-orphans (Thurman, et al, 2006;Operario et al, 2007;Nyamu-kapa et al, 2008;Birdthistle et al, 2009). It is possible that HIV infection among adults is households will lead to an increased risk of adolescents engaging in high-risk sexual behaviors due to homes being destabilized or impoverished by HIV/AIDS (Enaik et al, 2002;Oman et al, 2005;Sturgeon, 2008).…”
Section: Discussionsupporting
confidence: 73%
“…A number of recent studies in various Southern Africa settings have observed greater sexual risk (ever had sex, ever pregnant) among orphans than non-orphans (Thurman, et al, 2006;Operario et al, 2007;Nyamukapa et al, 2008;Birdthistle et al, 2009). Birdthistle et al, (2009) noted that educational status explained only a small part of double orphans sexual risk and that additional research is needed to identify other socio-economic and emotional factors driving orphans sexual risk so that prevention and support programmes can meet the needs of this growing population.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the two studies from Zimbabwe found that female orphans were also more likely to have experienced other STI symptoms. Several crosssectional studies from South Africa, Kenya and Zimbabwe report that orphan children are more likely to have had sex than non-orphans (Thurman et al 2006;Operario et al 2007;Juma et al 2007;7 Nyamukapa et al 2008). In a national household survey of South African young people, Operario et al (2007) found female orphans to be more likely to have had multiple sex partners than female non-orphans.…”
Section: Orphaningmentioning
confidence: 99%
“…Several crosssectional studies from South Africa, Kenya and Zimbabwe report that orphan children are more likely to have had sex than non-orphans (Thurman et al 2006;Operario et al 2007;Juma et al 2007;7 Nyamukapa et al 2008). In a national household survey of South African young people, Operario et al (2007) found female orphans to be more likely to have had multiple sex partners than female non-orphans. Furthermore, evidence of earlier sexual debut among orphans than nonorphaned children is provided by two recent reviews of Demographic and Household Survey (DHS) data sets from Lesotho, Malawi, Mozambique, Rwanda and Tanzania (Campbell et al 2008) 8 and from Lesotho, Mozambique, Tanzania and Uganda (Palermo and Peterman 2008).…”
Section: Orphaningmentioning
confidence: 99%
“…The analysis controlled for, but did not stratify by gender. Using a nationally representative survey of young people aged 15-24 in South Africa collected in 2003, Operario et al (2007) studied the association between orphanhood (also using an indicator of one or both parents deceased) and (a) sexual behaviours, and (b) HIV sero-status. Adjusting for other sociodemographic factors, parental death among females was significantly associated with HIV-positive status, ever having had sex, and having one or more sexual partners in the year before the survey.…”
Section: Orphanhoodmentioning
confidence: 99%